Women and development : the Indian experience - Seth, Mira (New Delhi : Thousand Oaks, Calif. : Sage, 2001)
"This book is a comprehensive and analytical account of women's development programmes since India's independence. Replete with comparisons from around the world, it discusses the status of Indian women based on regional, religious, caste and class divides." "This book is written from the perspective of a development administrator who has taken an active part in many of these processes - in the role of a policy maker, planner and actual implementer of programmes for women's development. It will be of interest to government agencies, non-governmental organisations, social workers and those in the fields of gender studies, policy and planning, family planning and welfare, and human resource development."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Women in development -- India